2022
DOI: 10.3390/nu14122504
|View full text |Cite
|
Sign up to set email alerts
|

The Microalgae Phaeodactylum tricornutum Is Well Suited as a Food with Positive Effects on the Intestinal Microbiota and the Generation of SCFA: Results from a Pre-Clinical Study

Abstract: Microalgae such as Phaeodactylum tricornutum (PT) are a sustainable source of nutrients, especially eicosapentaenoic acid (EPA), fucoxanthin (Fx), and chrysolaminarin (Chrl), the concentrations of which can vary depending on the culture conditions. We generated three types of diets containing either an EPA- and Fx-rich (EPA/Fx) or Chrl-rich microalgae (with 5, 15, or 25% added to the diet) or an isocaloric control diet (CD). These diets were evaluated over 14 days in young C57BL/6J mice for safety and bioavail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 79 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…revealed their antioxidant activity and inhibition of angiotensin-converting enzyme (ACE), suggesting diatom lipids as alternative ACE inhibitors or food supplement for cardiovascular disease prevention due to the role played by this enzyme in hypertension and other cardiovascular disorders [ 61 ]. Another recent paper by Stiefvatter and collaborators [ 62 ] describes a pilot trial on 19 healthy elderly individuals (12 females and 7 males) receiving supplementation with EPA-rich microalga Phaeodactylum tricornutum for two weeks. Analyzing anti-inflammatory and antioxidative parameters, this study suggested potential useful activity of the diatom for pursuing healthy aging.…”
Section: Primary Metabolitesmentioning
confidence: 99%
“…revealed their antioxidant activity and inhibition of angiotensin-converting enzyme (ACE), suggesting diatom lipids as alternative ACE inhibitors or food supplement for cardiovascular disease prevention due to the role played by this enzyme in hypertension and other cardiovascular disorders [ 61 ]. Another recent paper by Stiefvatter and collaborators [ 62 ] describes a pilot trial on 19 healthy elderly individuals (12 females and 7 males) receiving supplementation with EPA-rich microalga Phaeodactylum tricornutum for two weeks. Analyzing anti-inflammatory and antioxidative parameters, this study suggested potential useful activity of the diatom for pursuing healthy aging.…”
Section: Primary Metabolitesmentioning
confidence: 99%
“…This way, the algal biomass is maximally exploited, which leads to optimal economic and environmental efficiency. P. tricornutum has several marketable high‐value products: the pigment fucoxanthin, polyunsaturated eicosapentaenoic fatty acid (EPA) and laminarin, a β ‐glucan polysaccharide with health‐supporting properties 13 …”
Section: Biorefinery Optimizationmentioning
confidence: 99%
“…P. tricornutum has several marketable high-value products: the pigment fucoxanthin, polyunsaturated eicosapentaenoic fatty acid (EPA) and laminarin, a βglucan polysaccharide with healthsupporting properties. 13 For the cultivation of P. tricornutum in pasteurized sea water, we consider three alternative N-sources (NaNO 3 , NaNO 2, and urea). 14 Seawater is one important makeup flow into the system.…”
Section: Biorefinery For Wet Algal Biomassmentioning
confidence: 99%
“…It is important to note that microalgae have no common pathogens with humans and some have already been approved by the FDA as human food. Although the whole P. tricornutum is not approved as human food yet, its nutritional composition is highly similar to the microalga Odontella aurita that was recently approved by European Food Safety Authority (EFSA) [107]. These microorganisms could be grown in closed/controlled bioreactors, which precisely meet the requirements of good manufacturing practice (GMP) for the recombinant proteins produced [21].…”
Section: Edible Microalgae As a Biosystem For Production And Delivery...mentioning
confidence: 99%